2019
DOI: 10.1021/acs.organomet.9b00095
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine(diimine) Chelate Hydrogenation in a Molybdenum Nitrido Ethylene Complex

Abstract: Addition of H2 gas to the aryl-substituted pyridine­(diimine) molybdenum nitride ( iPrPDI)­Mo­(N)­(C2H4) ([1-(N)­(η 2 -C 2 H 4 )]; iPrPDI = 2,6-(2,6-iPr2-C6H3NCMe)2C5H3N) in the presence of the rhodium hydride precatalyst (η5-C5Me5)­(py-Ph)­Rh­(H) ([Rh–H]; py-Ph = 2-phenylpyridine) resulted in partial hydrogenation of the central pyridine of the iPrPDI chelate to yield ( iPrTHPDI)­Mo­(N)­(C2H4) ([2-(N)­(η 2 -C 2 H 4 )]; iPrTHPDI = 2,6-(2,6-iPr2-C6H3NCMe)2C5H6N). The product, [2-(N)­(η 2 -C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…In each case, the IBO corresponding to the analogous interaction in the metallophosphorane isomers 4′ – 6′ (Figure A–C, right) indicates an increased parity of distribution across the P–M bond (e.g., P = 1.154, Pd = 0.815; Figure B, right) as in an X-type normal covalent bond. Additionally, localized orbital bonding analysis (LOBA) was performed to assign the intuitive oxidation states (OSs) of the metal centers . For all of the compounds in Figure , four doubly occupied metal-based orbitals corresponding to the nonbonding d valence set were identified.…”
supporting
confidence: 74%
“…In each case, the IBO corresponding to the analogous interaction in the metallophosphorane isomers 4′ – 6′ (Figure A–C, right) indicates an increased parity of distribution across the P–M bond (e.g., P = 1.154, Pd = 0.815; Figure B, right) as in an X-type normal covalent bond. Additionally, localized orbital bonding analysis (LOBA) was performed to assign the intuitive oxidation states (OSs) of the metal centers . For all of the compounds in Figure , four doubly occupied metal-based orbitals corresponding to the nonbonding d valence set were identified.…”
supporting
confidence: 74%
“…33−35 Indeed, in 2019 the Chirik group found that RhH-1 can catalyze the hydrogenation to ammonia of amides, 36 nitrides, 37 and related ligands. 38 Very recently, the use of the same precatalyst for the hydrogenation of N-heteroarenes has been reported by the same group. 39 They have proposed that, upon heating or irradiation, the reductive elimination of 2-phenylpyridine from RhH-1 can lead to the formation of catalytically active multimetallic clusters (and eventually nanoparticles), under varied H 2 pressures (4−36 atm) at elevated temperatures (80−100 °C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…catalysts that they had used for H· transfer from H 2 to solve this problem, but neither gave any 2 from 1 . We then considered (η 5 -C 5 Me 5 )­Rh­(ppy)H (ppy = 2-(2-pyridyl)­phenyl), RhH-1 , developed in the Norton laboratory and shown to be a fast hydride and hydrogen atom donor, but a relatively poor proton donor (Scheme B). , Related Cp*Rh systems have been shown to effectively catalyze arene and olefin hydrogenation. Indeed, in 2019 the Chirik group found that RhH-1 can catalyze the hydrogenation to ammonia of amides, nitrides, and related ligands . Very recently, the use of the same precatalyst for the hydrogenation of N -heteroarenes has been reported by the same group .…”
Section: Introductionmentioning
confidence: 99%
“…Noninnocent ligands that directly participate in redox chemistry are particularly noted for their ability to augment metal-based electron transfer and the resulting tendency to promote novel reactivity modes . Ligands based upon the workhorse 2,2′-bipyridyl (bpy) and pyridinediimine (PDI) cores are two such platforms, in which low-lying π* molecular orbitals help stabilize reduced metal complexes . PDI-based ligands can undergo multiple reduction events, obviating the need for metal-centered ET processes .…”
Section: Introductionmentioning
confidence: 99%